Effect of General Anesthesia vs. Conscious Sedation on the Outcomes of Acute Ischemic Stroke Patients After Endovascular Therapy: A Meta-Analysis of Randomized Clinical Trials - Wan, Teng-Fei; Zhang, Jian-Rong; Liu, Liang (Frontiers in Neurology, 2019)
Background: Endovascular therapy is the standard treatment for acute ischemic stroke (AIS) patients caused by a large vessel occlusion in the anterior circulation, whereas the impacts of general anesthesia (GA) versus conscious sedation (CS) for such procedures remained as a continued debate. Methods: We systematically searched PubMed, Embase and ClinicalTrials.gov. We restricted our search to RCTs that examined the clinical outcomes of endovascular therapy with GA vs CS. The Cochrane Risk of Bias Tool was used to assess study quality. Random-effects or fixed-effects meta-analyses were used for evaluating all outcomes. Results: Total 3 randomized clinical trials met our inclusion criteria, with 368 individuals enrolled. Patients were randomized to receive GA or CS during endovascular therapy. In a meta-analysis of these trials, patients in the GA group were associated with favorable functional outcome (mRS score ≤ 2) compared with the CS group (pooled OR = 1.81, 95% CI: 1.17-2.79, P = 0.008). Besides, patients in the GA group had higher odds of successful reperfusion (pooled OR = 1.80, 95% CI: 1.05-3.08, P = 0.033), but no significant differences were seen in symptomatic intracranial hemorrhage (pooled OR = 0.54, 95% CI: 0.11-2.57, P = 0.308), vessel dissection or perforation (pooled OR = 1.38, 95% CI: 0.30-6.31, P = 0.679), migration of embolus to a new territory (pooled OR = 2.28, 95% CI: 0.89-5.87, P = 0.085), postoperative pneumonia (pooled OR = 1.74, 95% CI: 0.76-4.01, P = 0.149) and all-cause mortality at 90 days (pooled OR = 0.73, 95% CI: 0.43-1.26, P = 0.263) compared with the CS group. Conclusion: Performing endovascular therapy with GA, compared with CS, improves functional independence after 90 days significantly for patients with AIS caused by a large vessel occlusion in the anterior circulation. However, additional lager and multi-center randomized controlled trials to definitively confirm our findings are warranted for the limitation of the small sample size in this study.